Mundania: How and Where Technologies Are Made Ordinary - Willim, Robert (Bristol University Press, 2024)
Available open access digitally under a CC-BY-NC-ND license. Digital services, platforms and arrangements are often promoted as smooth and convenient, smart or intelligent. When introduced, devices can appear utterly fascinating or awkward, even disquieting. Eventually, however, they soon disappear in the muddle of everyday life. This is how Mundania takes form. Based on original research, this book uses the concept of mundania to better understand technological change. Scholar-artist Robert Willim deftly unpacks the interplay between everyday life and the immense complexity of technological infrastructures. Offering imaginative new insights into our relationship with technology, this book will appeal to readers in a range of fields from science and technology studies and media studies to the arts.